PERUBAHAN LOYALITAS ELIT PARTAI POLITIK (STUDI: PERPINDAHAN ELITPARPOL GOLKAR DAN NASDEM PADA PILEG 2019 DI KOTA DENPASAR) - Pangesti, Ajeng Widjaya; Ali Azhar, Muhammad; Mahaswari. J.M, AA. Sagung Mirah (Jurnal Nawala Politika, 2019)
ABSTRACT   The study aims to determine changes in loyalty that occur to elite political parties in the city of Denpasar. Research using Rational Choice Theory James S. Coleman, This type of research is a qualitative descriptive study. Research findings, First: ideology becomes the basis of a political elite losing its loyalty to the party, Second: pragmatic, that is, with the interests brought by the elite when moving parties, Third: power is a reason often used by elites losing their loyalty, the elite assume that the previous party was not get a position in accordance with the wishes of the elite, the fourth economy is one of the driving factors that occur among the elite political parties, because the party was allegedly able to provide financial support, the latest figures, figures are figures that can be used as a reference in various political activities and decisions political. Keywords : changes in loyalty, elite, political parties.